2(12b+7)+9b-1=180-9b-1

Simple and best practice solution for 2(12b+7)+9b-1=180-9b-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(12b+7)+9b-1=180-9b-1 equation:


Simplifying
2(12b + 7) + 9b + -1 = 180 + -9b + -1

Reorder the terms:
2(7 + 12b) + 9b + -1 = 180 + -9b + -1
(7 * 2 + 12b * 2) + 9b + -1 = 180 + -9b + -1
(14 + 24b) + 9b + -1 = 180 + -9b + -1

Reorder the terms:
14 + -1 + 24b + 9b = 180 + -9b + -1

Combine like terms: 14 + -1 = 13
13 + 24b + 9b = 180 + -9b + -1

Combine like terms: 24b + 9b = 33b
13 + 33b = 180 + -9b + -1

Reorder the terms:
13 + 33b = 180 + -1 + -9b

Combine like terms: 180 + -1 = 179
13 + 33b = 179 + -9b

Solving
13 + 33b = 179 + -9b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '9b' to each side of the equation.
13 + 33b + 9b = 179 + -9b + 9b

Combine like terms: 33b + 9b = 42b
13 + 42b = 179 + -9b + 9b

Combine like terms: -9b + 9b = 0
13 + 42b = 179 + 0
13 + 42b = 179

Add '-13' to each side of the equation.
13 + -13 + 42b = 179 + -13

Combine like terms: 13 + -13 = 0
0 + 42b = 179 + -13
42b = 179 + -13

Combine like terms: 179 + -13 = 166
42b = 166

Divide each side by '42'.
b = 3.952380952

Simplifying
b = 3.952380952

See similar equations:

| Y+20=4y-15 | | -2x+12+3x=2+x+10 | | 5-7(2-x)=31-4(x-5) | | 6(x-2)-(x+2)=3x-18 | | 5(x+5)-20=0 | | 123=5x+6(2x-5) | | -2(x-2)-4x=3(x+10)-9x | | 5x-8c=-6 | | -20=8x+2x | | 1-5n+5n-2=1+n-6 | | 7[3-4(x-1)]+6[(2x+7)+-8]=17x-333 | | 4(2w-5)=3w-13 | | 3/8x+16=19 | | 5+2(x)=3(x) | | -4(t-3)=5(-2t+4) | | -6h+3=21 | | -8(4+9r)=7(r-11r) | | 12-x=8x+4 | | 6*7-8=7 | | 8(x-2)=8x | | 2x-2=5x+8 | | 12x+17=13x+1 | | -7x-9=-23 | | w^2-7w-110=0 | | -12+3/4x=3 | | 4n+14=6n | | 5g+4y(-5+3g)=16g | | 9x+11=-1x-5 | | 12(x+2)=2(6x-4)+32 | | 7(2c-5)=25 | | -7392(18x-172)=0 | | 2x+3=2x-(3x+2)+6 |

Equations solver categories